2003
DOI: 10.1023/b:jobb.0000008032.49504.48
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Operated Calcium Channel Heterogeneity in Pancreatic   Cells: Physiopathological Implications

Abstract: Voltage-operated calcium channels play crucial roles in stimulus-secretion coupling in pancreatic beta cells. A growing body of evidence indicates that these channels in beta cells are heterogeneous. In particular, not all the high-threshold calcium channels expressed belong to the best known L-type. In rat insulinoma cells, for example, L, N, and P/Q-type channels are present, while in human beta cells L-type and P/Q-type dominate. Where present, N-type and P/Q-type channels participate, alongside with the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 79 publications
0
34
0
Order By: Relevance
“…For example, it has been reported that, in mouse ␤-cells, the ␣1C subunit is necessary for the first phase of secretion (35), whereas the ␣1D subunit participates mainly in response to 3 mM glucose (41). Moreover, the latter could be important for postnatal ␤-cell generation (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that, in mouse ␤-cells, the ␣1C subunit is necessary for the first phase of secretion (35), whereas the ␣1D subunit participates mainly in response to 3 mM glucose (41). Moreover, the latter could be important for postnatal ␤-cell generation (27).…”
Section: Discussionmentioning
confidence: 99%
“…␤-Cells from different species express different ␣1 subtypes; for example, adult rat ␤-cells express ␣1 subunits responsible for generating the T, L, P/Q, and R types of VGCC (25). The ␣1 subunit that underlies the T-type Ca 2ϩ current recorded in these cells corresponds to the ␣1G subunit (Cav3.1), which has been isolated and cloned in ␤-cells (39,41,52).…”
mentioning
confidence: 99%
“…Voltage-gated Ca 2ϩ channels are activated by coordinated fluctuations of the cell membrane potential (electrical activity), which are initiated by the glucose-induced closure of ATP-sensitive K ϩ channels (K ATP channels) (2,3) and dependent on voltagegated Na ϩ and K ϩ channels (4). Due to the limited availability of human islets, few electrophysiological studies of voltage-gated ion channels in human ␤-cells have been published, and the identity of the ␤-cells was not unequivocally established (5)(6)(7)(8), although 45% of normal human islets cells are non-␤-cells (9). In some earlier studies (10 -12), identification of ␤-cells was based on the presence of K ATP currents.…”
Section: Conclusion-voltage-gated T-type and L-type Ca 2ϩ Channels Amentioning
confidence: 99%
“…Although expression of P/Q-type Ca 2ϩ channels in human ␤-cells has been reported earlier (8), their relative contribution to the total Ca 2ϩ current and their function in stimulus secretion coupling have been unclear. We now show that P/Q-type Ca 2ϩ channels account for ϳ45% of the integrated whole-cell Ca 2ϩ current and that they play a critical role in depolarization-evoked exocytosis and glucose-induced insulin secretion, especially at low glucose concentrations (6 mmol/l).…”
mentioning
confidence: 98%
“…The major dihydropyridine-sensitive calcium channels in rat b-cells are Ca V 1.2 or Ca V 1.3, with different studies emphasising the role of either one (Iwashima et al 1993, Liu et al 2004, Taylor et al 2005. Ca 2C currents that can be inhibited by u-conotoxin GVIA, which is known to block Ca V 2.2, have been reported in rat b-cells, but their role in insulin secretion is controversial (Satin et al 1995, Sher et al 2003. Ca V 2.3, which is inhibited by SNX-482, accounts for another 18% of the Ca 2C current in mouse b-cells ( Jing et al 2005).…”
Section: Introductionmentioning
confidence: 99%